The Head Pendant from the Marchetti Collection: Phoenicio-Punic Glass or Modern Forgery? - Elisabetta Malaman; Cinzia Bettineschi; Ivana Angelini; Monica Salvadori (Applied Sciences)
This article focuses on the archaeological and archaeometric characterization of a glass head pendant in Phoenicio-Punic style from the Marchetti Collection, a formerly private assemblage now belonging to the University of Padova. After the first visual inspection, the typology and appearance of the object raised serious doubts about its authenticity. For this reason, an integrated approach combining stylistic and typo-chronological analyses with archaeometric data was implemented for reconstructing the manufacturing techniques and identifying the raw materials used (i.e., silica source, flux composition, and colouring and opacifying agents). The analytical techniques used include stereomicroscopy (SM) to identify the production techniques, OM, SEM-EDS, and µ-Raman for textural and chemico-mineralogical investigations. The archaeological study and the comparison of our analytical results with the data published in the scientific literature agree in confirming that the investigated object is a forgery, as already demonstrated for other pieces from the same collection.